Digital libraries - Arms, William Y. (MIT Press, 2000)
The emergence of the Internet and the wide availability of affordable computing equipment have created tremendous interest in digital libraries and electronic publishing. This book is the first to provide an integrated overview of the field, including a historical perspective, a survey of the state of the art, and an examination of current research.
Keywords: Libraries -- United States -- Special collections -- Electronic information resources.; Digital libraries -- United States.; elektronické knihy; electronic books